Unions and income inequality: A heterogeneous panel cointegration and causality analysis - Dierk Herzer (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2014)
Although a large body of research has examined the effects of unions on the wage distribution, surprisingly little attention has been devoted to the effects of unions on the distribution of income. This paper examines the long-run relationship between unionization and income inequality for a sample of 20 countries. Using heterogeneous panel cointegration techniques, we find that (i) unions have, on average, a negative long-run effect on income inequality, (ii) there is considerable heterogeneity in the effects of unionization on income inequality across countries (in about a third of cases the effect is positive), and (iii) long-run causality runs in both directions, suggesting that, on average, an increase in unionization reduces income inequality and that, in turn, higher inequality leads to lower unionization rates.
Keywords: J51; D31; C23; 330; unions; income inequality; cross-country heterogeneity; causality; panel cointegration